1998
DOI: 10.3354/meps170239
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and tidal vertical migration of pre-settlement King George whiting Sillaginodes punctata in relation to feeding and vertical distribution of prey in a temperate bay

Abstract: Vertically stratified sampling was undertaken for pre-settlement K n g George whiting Sillaglnodespunctata at 1 site in 1995 and 4 sites in 1996, in Port Phillip Bay, Australia. In 1995, 3 depth strata were sampled: surface, 2.5-3.0 m, and 5.0-5.5 m, in a total water depth of 7 to 8 m. Samphng was conducted on 17 dates and encon~passed all combinations of day and night, and ebb and flood tide. A total of 3, or in one case 4, replicate samples were taken at each depth. On 4 occasions a smaller zooplankton net w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…Reverse diel migration can result from active selection of near surface waters during the day and random dispersal or sinking at night (Neilson and Perry 1990). This strategy has been hypothesized to improve feeding success because light levels for visually foraging fishes are higher near the surface; the strategy has also been hypothesized to help these fishes avoid predation (Ohman et al 1983;Jenkins et al 1998). Stomach content and laboratory observations of the endangered delta smelt suggest they are visual foragers and do not feed nocturnally (Bennett et al unpubl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse diel migration can result from active selection of near surface waters during the day and random dispersal or sinking at night (Neilson and Perry 1990). This strategy has been hypothesized to improve feeding success because light levels for visually foraging fishes are higher near the surface; the strategy has also been hypothesized to help these fishes avoid predation (Ohman et al 1983;Jenkins et al 1998). Stomach content and laboratory observations of the endangered delta smelt suggest they are visual foragers and do not feed nocturnally (Bennett et al unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Of these four mechanisms, vertical migra- tion behavior is frequently studied. Often, in estuaries with semidiurnal or diurnal tidal cycles, a diel rhythm coincides with tidal migrations such that movements to surface waters occur on nightly flood tides with organisms remaining at depth during daytime ebbs (Weinstein et al 1980;Christy and Morgan 1998;Forward et al 1998;Jenkins et al 1998;Kimmerer et al 1998).…”
mentioning
confidence: 99%
“…For 2 sampling times in different years, larvae ag- gregated during the day around 4 m at our sampling site, which had a maximum depth of 12 m. Aggregation during the day and nocturnal diffusion have been seen in other marine fish larvae, including sandeel (Jensen et al 2003), King George whiting Sillaginodes punctata (Jenkins et al 1998) and herring Clupea harengus (Haslob et al 2009). However, nocturnal ascent, rather than nocturnal diffusion, is more commonly seen in other larval sparid species, including the closely related Pagrus major (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…Although a relationship between prey density and larval DVM behaviour has been found for numerous taxa, for example herring Clupea harengus (Munk et al 1989), sandeel Ammodytes marinus (Jensen et al 2003) and mackerel Scomber scombrus (De La Fontaine & Gascon 1989), other studies have found no such relationship (e.g. Brewer & Kleppel 1986, Jenkins et al 1998. However, the relationship between prey availability and DVM may be more complicated where it is not just the availability of prey that is important, but rather, the ability of fish larvae to obtain high foraging success in relation to multiple environmental factors (Munk et al 1989).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation